P11 A systematic review of the reporting of robotic cholecystectomy. (8th April 2021) - Higginbotham, G; Hollowood, F; Lok, P; Turner, B; Gull, E; Kirkham, E N; ,
Abstract: Introduction: Robotic cholecystectomy (RC) is reported to be an innovative alternative to laparoscopic cholecystectomy for the surgical management of gallbladder disease. Perceived technical benefits of RC include enhanced ergonomic capabilities and visualisation. Whilst RC is becoming increasingly widespread, there is a paucity of high-quality data supporting its use, and conflicting evidence of outcomes in current literature. With accumulating reports citing complications associated with novel invasive procedures, experts have suggested that robust clinical evaluation is required. It is vital that techniques such as RC are evaluated consistently, in order for surgeons to fully educate patients about the treatment and obtain informed consent. This study aims to summarise and appraise the reporting of studies of RC. Methods: Systematic searches identified all published studies reporting RC. Data collection was based on the IDEAL (Idea, Development, Exploration, Assessment, Long-term follow-up) framework. This will be used to identify key areas of reporting including; general study characteristics, patient selection, regulatory and governance arrangements, operator and centre expertise, technique description, and outcome reporting. Because the study will not aim to draw conclusions about the effectiveness of robotic surgery, meta-analyses will not be not performed. Results: Systematic searches identified 1425 abstracts; 90 full-text papers were included. Results will be summarised in a narrative synthesis and further data will be analysed prior to presentation. Conclusion: This in-depth analysis of the published literature on RC will provide evidence to understand how this innovative procedure has been introduced and evaluated in relation to the IDEAL recommendations.